2006
DOI: 10.1038/laban0206-23
|View full text |Cite
|
Sign up to set email alerts
|

Restraint collars. Part I: Elizabethan collars and other types of restraint collars

Abstract: Restraint collars can provide an investigator with a noninvasive means to prevent certain undesirable behaviors and provide a clinician with a nonpharmaceutical method to prevent an animal from inflicting self-injury; without proper use and monitoring, however, these collars can do more harm than good. This first part of our look at restraint collars introduces collar types and proper use. Next month's installment will review specific issues associated with the use of different types of collars for different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 11 publications
2
26
0
Order By: Relevance
“…33 Stress hormone levels measured over time can confirm the adjustment period required for adapting to a collar. 1 In one study, the normal corticosterone level in mice was below 5 ng/mL, although it was over 15 ng/mL during stress. 33 In this study, the stress hormone levels showed no significant differences among groups (Figure 3b).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…33 Stress hormone levels measured over time can confirm the adjustment period required for adapting to a collar. 1 In one study, the normal corticosterone level in mice was below 5 ng/mL, although it was over 15 ng/mL during stress. 33 In this study, the stress hormone levels showed no significant differences among groups (Figure 3b).…”
Section: Discussionmentioning
confidence: 96%
“…Investigators are occasionally required to prevent certain animal behaviours during experiments, such as coprophagy, self-grooming, self-injury, licking of test compounds or post-surgical sites and removal of catheters, plasters and bandages. 1,2 Infection of wounds and post-surgical sites is common, and test compounds are often removed by continuous grooming. 3 To prevent such events from occurring, investigators use various restraint collars for experimental animals.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Occasionally patients may require a restraint collar to prevent them from dislodging the sutures 7,8 . Animal caretakers should be sure food and water are easily accessible.…”
Section: Postoperative Considerationsmentioning
confidence: 99%